STRATEGI DAN MOTIVASI UNTUK MENINGKATKAN KEPATUHAN PAJAK KENDARAAN BERMOTOR PAJAK MASYARAKAT DI DKI JAKARTA: STRATEGY AND MOTIVATION TO IMPROVE MOTOR VEHICLE TAX COMPLIANCE OF THE COMMUNITY IN DKI JAKARTA - Ferawati, Ferawati; Magdalena, Febriani Cristina Susianti (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This research aims to determine the effect of motor vehicle tax waiver policy, Transfer of Title Fee Exemption, E-Samsat System, and Motivation on vehicle tax payer compliance in DKI Jakarta. A quantitative methodological framework was adopted, involving the administration of questionnaires to a sample of 146 vehicle proprietors. The data was subjected to multiple linear regression analysis for comprehensive evaluation. The findings indicate that the motor vehicle tax waiver policy, Transfer of Title Fee Exemption, and motivational factors exert a positive influence on the compliance of vehicle taxpayers. Nevertheless, while the Transfer of Title Fee Exemption demonstrates a positive yet statistically insignificant effect, the E-Samsat System exhibits an insignificant impact on the compliance of vehicle taxpayers